2017
DOI: 10.1159/000479527
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Stereotactic Accuracy in Image-Guided Deep Brain Stimulator Electrode Placement

Abstract: Background/Aims: Intraoperative imaging allows near-real-time assessment of stereotactic accuracy during implantation of deep brain stimulation (DBS) electrodes. Such technology can be used to examine factors impacting stereotactic error. Methods: Intraoperative CT imaging was reviewed in patients undergoing DBS placement at Oregon Health and Sciences University. Coordinates of the target electrode were compared to the operative plan to characterize the magnitude and direction of stereotactic error with respec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 13 publications
1
10
0
Order By: Relevance
“…The intended targets were GPi ( n = 86), STN ( n = 31), and Vim ( n = 52). The results indicated that the average Euclidean error was 1.63 mm (SD = 0.87) . However, the error magnitude was higher for Vim (1.95 mm, greater Euclidean error and greater medial deviation off target) than for GPi (1.44 mm), while STN (1.65 mm) did not differ from either Vim or GPi (ANOVA: F = 6.15, p = 0.003) .…”
Section: Surgical Techniquementioning
confidence: 89%
See 1 more Smart Citation
“…The intended targets were GPi ( n = 86), STN ( n = 31), and Vim ( n = 52). The results indicated that the average Euclidean error was 1.63 mm (SD = 0.87) . However, the error magnitude was higher for Vim (1.95 mm, greater Euclidean error and greater medial deviation off target) than for GPi (1.44 mm), while STN (1.65 mm) did not differ from either Vim or GPi (ANOVA: F = 6.15, p = 0.003) .…”
Section: Surgical Techniquementioning
confidence: 89%
“…The main advantage of placing DBS electrodes using iMRI is the ability to visualize the intended target and this allows for precise implantation and adjustment of electrode trajectories before final placement . One study evaluated the effect of target selection on the accuracy of electrode placement in asleep DBS for the treatment of movement disorders . The study examined 169 leads in 94 patients using intraoperative imaging.…”
Section: Surgical Techniquementioning
confidence: 99%
“…In a large-scale study of DBS patients who underwent surgery using iCT, there were greater Euclidean error and greater medial deviation in the trajectory targeting Vim. The authors found that there are systematic tendencies in stereotactic error that differ with respect to the structure targeted [70]. In the study analyzing stereotactic accuracy of iMRI, the DBS lead placement using iMRI guidance showed a radial targeting error of 0.6-1.2 mm, while the error using iCT was 0.8-1.24 mm [22,25,27,28,31,37,71].…”
Section: Targeting Accuracymentioning
confidence: 99%
“…Linear regression done on our data has shown statistical significance between the TPE and the trajectory angle on the bone surface, and the EPE and the trajectory angle on the bone surface. Previous research just stated that the direction of the trajectory or the angle of the trajectory had a great influence on the accuracy of the procedure, without giving an adequate description of the methodology and measurements 3,38–41 . We noticed that a larger size angle on the bone caused greater displacement of the drill bit due to a greater magnitude of shear force, which increased the EPE.…”
Section: Discussionmentioning
confidence: 83%
“…Bleeding originating from superficial vessels may be the cause of EPE and that originating from vessels on the trajectory path and on the biopsy site may be the cause of TPE. Several papers report the correlation between the EPE or TPE and the angle of trajectory on the skull; however, the angle of the trajectory is defined as the deviation of the angle on the coronal or the sagittal plane 40–42 . We made a multiplanar reconstruction through the entry point on the skull and measured the largest deviation of the angle (Figure 3).…”
Section: Discussionmentioning
confidence: 99%